Hedyn - Lewis, Caryl (Y Lolfa, 2022)
This is the first novel for this age by this prolific author. On his birthday, Marty receives a gift from his grandfather - a magical seed. Humorous and unusual, this story about making dreams come true will inspire and raise serious topics. Suitable for 9-12 year old readers.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books